(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: on 3/13/2020, the first cases of SARS Cov-2 infection were detected in Uruguay. In 2021, cases increased steadily, negatively impacting the health system that was reorganized. The British Hospital (HB), a private health organization at tertiary level started to work in a coordinated way at its 3 levels of care. They created a specific team to help improve the monitoring of suspected/confirmed cases. It has 7,922 users under the age of 15. Objective: describe the evolution of COVID-19 cases in patients aged 0-15 years assisted at the HB between August 1st, 20 and May 31st, 2021, assessing demographic, clinical and epidemiological aspects. Material and methods: retrospective descriptive study. The longitudinal follow-up record of pediatric users with microbiologically confirmed COVID-19 was analyzed. Results: 370 patients were included (51.5% female and 48.5% male), distributed by age groups (6.5% <1 year, 31.6% 1-5, 32.9% 6-10, 28.8% 11-15 years). In 2020, 50 cases were diagnosed, and 320 in 2021. 58.9% presented at least one symptom; fever (59%), followed by rhinorrhea, cough, and sore throat. Home infection in 66.5%, 16.7%, school infections (IE), 11.1% during social activities, 0.8% in sports clubs, and 4.8% with no epidemiological link. Index case: an adult in 80.3% and another child in 19.7%. 9% of the study patients generated secondary case/s, home infections 90% (mother 66.7%, father 54.5%, sibling 42.4%). Information on secondary cases in IE, clubs or school transportations could not be obtained. All presented good evolution, 2 were hospitalized. No deaths. Conclusions: pediatric COVID-19 increased considerably in the 2nd quarter of 2021. As in other series, 40% asymptomatic, mostly home contagion from adults. 9% generated secondary cases showing a lower contagion of the pediatric population.